PENGARUH STRATEGI BISNIS, PERTUMBUHAN PENJUALAN, DAN INVENTORY INTENSITY TERHADAP PENGHINDARAN PAJAK PADA PERUSAHAAN CONSUMER NON CYCLICAL YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2018 – 2022 - Muhamad Ridwan; Neneng Hasanah (Publika Citra Media, 2024)
This research aims to determine the influence of Business Strategy, Sales Growth,and Inventory Intensity towards Tax Avoidance in companies consumer noncyclical 2018-2022. The population used in this research is the company consumernon cyclical listed on the IDX in 2018-2022. The sample used in this research was13 sample companies with a research observation period of 5 years in the 2018-2022 period and the number of financial reports sampled in this research was65.This research also analyzes data using panel data regression on EViews version12 software. The results of this research show that business strategy and salesgrowth influence tax avoidance. Temporary,inventory intensity has no effect on taxavoidance. However, simultaneously Business Strategy, Sales Growth,andInventory Intensity have a simultaneous effect on tax avoidance